VORTEX FLOW WINGS - Udartsev, Eugene; Rozbytskyi, Volodymyr; Sattarov, Artemii (Proceedings of National Aviation University (archive), 2019)
The paper presents an analysis of two alternative methods of influence on integral aerodynamic characteristics at large angles of attack with global flow separation. Firstly, the approach related to flat low-profile turbulators is reviewed. Then the leading edge vortex generators (LEVGs) of complex volumic shape are introduced as a more recent and efficient approach. It is explained how vortices generated at the upper surface shaped in a special way reach the trailing edge region and change conventional vortex pattern of the wing. The last section is devoted to a numerical modelling of vortex flow wings of unmanned aerial vehicles (UAVs).